siRNA Design Methods and Protocols - Taxman, Debra J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The discovery of RNA interference (RNAi) as a methodology for gene silencing has revolutionized biological research, providing an invaluable avenue for therapeutics, and small interfering RNA (siRNA) is the most common strategy utilized for enacting RNAi.  siRNA Design: Methods and Protocols offers expertly crafted guidelines and protocols for the selection of siRNA targeting sequences, for the strategic incorporation of chemical modifications, and for advantageous structural modifications to the classic siRNA design. Protocols are provided for using endogenous cellular machinery to produce siRNA from optimized precursor short hairpin RNA (shRNA) and artificial microRNA (amiRNA) molecules. Strategies are also described for specific applications such as immunostimulatory siRNA that may provide therapeutic benefit against viral infections in mammals, the simultaneous targeting of multiple siRNAs, and siRNA-mediated crop virus resistance.  The design of RNAi for gene silencing in embryonic, invertebrate, and plant systems requires a variety of unique approaches, several of which are described towards the end of this volume.  Written for the highly successful Methods in Molecular Biology™ series, this work contains the kind of detailed description and implementation advice that guarantees successful results.   Authoritative and easy to use, siRNA Design: Methods and Protocols will provide researchers, educators, clinicians, and biotech specialists with a broad understanding of the issues in RNAi and how they can be overcome strategically through design.
What Parameters to Consider and Which Software Tools to Use for Target Selection and Molecular Design of Small Interfering RNAs -- Methods for Selecting Effective siRNA Target Sequences Using a Variety of Statistical and Analytical Techniques -- Designing Functional siRNA with Reduced Off-Target Effects -- Design and Screening of siRNAs Against Highly Structured RNA Targets -- Engineering Small Interfering RNAs by Strategic Chemical Modification -- The Design, Selection and Evaluation of Highly Specific and Functional siRNA Incorporating Unlocked Nucleobase Analogs -- The Design, Preparation, and Evaluation of Asymmetric Small Interfering RNA for Specific Gene Silencing in Mammalian Cells -- Design of Nuclease-Resistant Fork-Like Small Interfering RNA (fsiRNA) -- Designing Dual-Targeting siRNA Duplexes Having Two Active Strands that Combine siRNA and MicroRNA-Like Targeting -- Strategies for Designing and Validating Immunostimulatory siRNAs -- Designing Efficient and Specific Endoribonuclease Prepared siRNAs (esiRNAs) -- Short Hairpin RNA-Mediated Gene Silencing -- Design of Lentivirally Expressed siRNAs -- Bi-Functional Short Hairpin RNA (bi-shRNA): Design and Pathway to Clinical Application -- Design and Chemical Modification of Synthetic Short shRNAs as Potent RNAi Triggers -- Production and Application of Long dsRNA in Mammalian Cells -- Design of RNAi Reagents for Invertebrate Model Organisms and Human Disease Vectors -- Construction of shRNA Expression Plasmids for Silkworm Cell Lines Using Single-Stranded DNA and Bst DNA Polymerase -- Designing Effective amiRNA and Multimeric amiRNA Against Plant Viruses -- Downregulation of Plant Genes with MiRNA Induced Gene Silencing.
Keywords: Biotechnology; Human genetics; Biotechnology; Human Genetics